Functional dichotomy between NKG2D and CD28-mediated co-stimulation in human CD8+ T cells. - Kamalakannan Rajasekaran; Va Xiong; Lee Fong; Jack Gorski; Subramaniam Malarkannan (PLoS ONE, 2010)
Both CD28 and NKG2D can function as co-stimulatory receptors in human CD8+ T cells. However, their independent functional contributions in distinct CD8+ T cell subsets are not well understood. In this study, CD8+ T cells in human peripheral blood- and lung-derived lymphocytes were analyzed for CD28 and NKG2D expression and function. We found a higher level of CD28 expression in PBMC-derived naïve (CD45RA+CD27+) and memory (CD45RA-CD27+) CD8+ T cells (CD28Hi), while its expression was significantly lower in effector (CD45RA+CD27-) CD8+ T cells (CD28Lo). Irrespective of the differences in the CD28 levels, NKG2D expression was comparable in all three CD8+ T cell subsets. CD28 and NKG2D expressions followed similar patterns in human lung-resident GILGFVFTL/HLA-A2-pentamer positive CD8+ T cells. Co-stimulation of CD28Lo effector T cells via NKG2D significantly increased IFN-γ and TNF-α levels. On the contrary, irrespective of its comparable levels, NKG2D-mediated co-stimulation failed to augment IFN-γ and TNF-α production in CD28Hi naïve/memory T cells. Additionally, CD28-mediated co-stimulation was obligatory for IL-2 generation and thereby its production was limited only to the CD28Hi naïve/memory subsets. MICA, a ligand for NKG2D was abundantly expressed in the tracheal epithelial cells, validating the use of NKG2D as the major co-stimulatory receptor by tissue-resident CD8+ effector T cells. Based on these findings, we conclude that NKG2D may provide an expanded level of co-stimulation to tissue-residing effector CD8+ T cells. Thus, incorporation of co-stimulation via NKG2D in addition to CD28 is essential to activate tumor or tissue-infiltrating effector CD8+ T cells. However, boosting a recall immune response via memory CD8+ T cells or vaccination to stimulate naïve CD8+ T cells would require CD28-mediated co-stimulation.